2016
DOI: 10.1111/jocd.12228
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and microbiological verification of the benefit of hair washing in patients with skin conditions of the scalp

Abstract: Proper hair washing improved scalp condition symptoms, and possibly the underlying etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…A disruption of the composition of the microbiome due to a change in scalp temperature often leads to detrimental scalp conditions by inducing dandruff. Thus, a change in scalp temperature can be a deciding factor of a healthy scalp …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A disruption of the composition of the microbiome due to a change in scalp temperature often leads to detrimental scalp conditions by inducing dandruff. Thus, a change in scalp temperature can be a deciding factor of a healthy scalp …”
Section: Resultsmentioning
confidence: 99%
“…People with sensitive scalps must pay greater attention to scalp health than those with non‐sensitive scalps, and using mild and low‐anionic surfactant products is recommended. Coacervates created with some scalp products cause irritation when they interact with water as a result of their particle structure; if they remain as a residue on the hair follicle or pores and then expand with water, this can help contaminants to penetrate and induce irritation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shampoo is one of the most suitable formulations for topical therapy and management of scalp psoriasis [5]. Kobayashi et al [6] found that proper hair washing improved scalp condition symptoms, and possibly the underlying etiology in patients with psoriasis; simple hair-washing techniques generally improved scalp conditions and decreased levels of the inflammatory markers IL-1 ra/IL-1α in the horny layer [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly to the analysis of IL-1α and/or IL-1RA, 9 articles used tape stripping to sample additional cytokines and chemokines (20-23, 34, 36-38, 40). The additional measurement of the total protein content on the tapes was used as a biomarker of the cohesiveness of the SC (20,27,36,40,41).…”
Section: Tape Strippingmentioning
confidence: 99%